Efficacy of entomopathogenic fungi, paecilomyces fumosoroseus, beauvena bassiana and metarhizium anisopliae var. majus against crocidolomia binotalis (Lepidoptera; Pyralidae) - N., Hashim; Y. B., Ibrahim (Universiti Putra Malaysia Press, 2003)
Laboratory bioassays of three local isolates of entomopathogenic hypomycetes against the cabbage-heart caterpillar, Crocidolomia binotalis Zeller (Lepidoptera: Pyralidae) and[reid efficacy ofseveralformulations ofPaecilomyces fumosoroseus (Wise) Brown and Smith were evaluated. Dosage-mortality bioassays revealed that all the isolates were able to cause mortality to second instar larvae. Majority of the larvae became moribund within two days after treatment. Exposures to doses varying from 2 x 1(jl conidia mLl to 2 x 107 conidia mLl resulted in mean larval mortalities from 10.3 to 100%. At concentrations exceeding 2 x lOS conidia mLl larval mortality was in excess of 80% and 100% mortality was observed at 2 x 107 conidia mLl for all three fungal species. Significant relationships (P<0.05) were obtained between log dosage and probit mortality for all the isolates. The EC5o for P. fumosoroseus was estimated at 1.926 x 1rY conidia mL1 , and was significantly lower than that ofBeauveria bassiana (Bals) Yuill at 5.038 x 103 conidia mL-l. The EC5o for Metarhizium anisopliae var majus (Metsch) Sorokin was significantly the highest, at 2.0 x 104 conidia mL-l. The best isolate was P.fumosoroseus which had LT50 almost half a day lower at a comparable dosage of 2 x107 conidia mLl, with a gradient of 4.656 as compared to 4.356 for B. bassiana and 4.193 for M. anisopliae var majus. In [reid treatments, plants were sprayed with suspensions containing 107 conidia mLl. Mean percent mortality for all the treatments were in excess of 70% and significantly higher (P<O. 05) than the control. Conidia in palm oil Vesawit® gave the most promising result against the cabbage-heart caterpillar.